2001
DOI: 10.1046/j.1440-1827.2001.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary low‐grade MALT lymphoma of the gallbladder

Abstract: We report a case of primary low-grade B-cell lymphoma of the mucosa-associated lymphoid tissue (low-grade MALT lymphoma) in the gallbladder. A 58-year-old woman suspected of gallbladder carcinoma underwent laparoscopic cholecystectomy. Microscopic examination of the gallbladder demonstrated lymphoid cell infiltration forming lymphoid follicles with hyperplastic secondary follicles. The surrounding monocytoid B cells and centrocyte-like cells selectively infiltrated the crypt epithelium forming lympho-epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The 36 patients with primary lymphoma of the gallbladder (Table 3) included 23 women and 13 men, aged 4 to 91 (mean 63) years. The most common lymphoma type was EMZL (12 cases)(1, 6, 7, 14, 35, 43, 45, 49, 53, 62, 66, 67), with an additional case from older literature (29) reported as “pseudolymphoma”. Collectively, these 13 patients were predominantly women (11/13) with a mean age of 68 years (range 31–91 years).…”
Section: Resultsmentioning
confidence: 99%
“…The 36 patients with primary lymphoma of the gallbladder (Table 3) included 23 women and 13 men, aged 4 to 91 (mean 63) years. The most common lymphoma type was EMZL (12 cases)(1, 6, 7, 14, 35, 43, 45, 49, 53, 62, 66, 67), with an additional case from older literature (29) reported as “pseudolymphoma”. Collectively, these 13 patients were predominantly women (11/13) with a mean age of 68 years (range 31–91 years).…”
Section: Resultsmentioning
confidence: 99%
“…Before the current report, only 9 cases of MALT lymphoma primarily involving the gallbladder and fulfilling confident diagnostic criteria have been described in the literature (Table 1) [5][6][7][8][9][10][11][12][13]. Overall, MALT lymphomas of the gallbladder appear to occur predominantly in elderly women (median age, 69.5 years; male to female, 1-4).…”
Section: Discussionmentioning
confidence: 97%
“…Of the few cases reported in the literature, none has been documented at the genetic level [5][6][7][8][9][10][11][12][13]. Here, we report a case of primary MALT lymphoma of the gallbladder with evidence of API2/MALT1 gene fusion, indicative of a t(11;18)(q21;q21) translocation.…”
Section: Introductionmentioning
confidence: 90%
“…Of these cases cases, six presented clinically with either an enlarged gall bladder with diffuse wall thickening or a probable mass lesion with or without portahepatic lymphadenopathy, mimicking gall bladder adenocarcinoma [2][3][4][5][6][7]. One of the cases as described by Tsuchiya et al showed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One of the cases as described by Tsuchiya et al showed Fig. 1 MALT lymphoma of gall bladder: a the polypoid lesion showing prominent full thickness circumferential involvement by atypical lymphoid infiltrate (H&E stain, ×20); b note the expanded marginal zone with a preserved germinal centre (H&E stain, ×100); c MALT lymphoma of gall bladder comprising a monomorphic population of small cleaved centrocyte-like cells admixed with a few larger blasts (H&E stain, ×400); d on higher magnification, the presence of lymphoepithelial lesions is seen (H&E stain, ×200); e lymphoepithelial lesion highlighted by AE1/AE3 immunostaining (×200); f strong and diffuse expression of CD20 by neoplastic lymphoid cells (×20); g BCL-2 expression by the neoplastic lymphoid cells and absent in the germinal centre (×20); h the neoplastic lymphoid cells showed membranous expression of IgM (×100) multiple polypoid lesions of gall bladder mucosa [6]. Similar lesions were also noted in the present case, but were focal and limited only to the gall bladder neck region.…”
Section: Discussionmentioning
confidence: 99%